Environmental politics and policy - Rosenbaum, Walter A. (Thousand Oaks, California : SAGE, 2014)
"Rosenbaum's classic, comprehensive text once more provides definitive coverage of environmental politics and policy, lively case material, and a balanced assessment of current environmental issues. The book sets needed context and describes the policy process, then covers specific environmental issues such as air and water pollution, toxic and hazardous substances, energy (both fossil fuel and nuclear), public lands, and climate change. Covering major environmental policy initiatives and controversies during President Obama's first term, and capturing the sudden and radical changes occurring in the American energy economy with fracking, the natural gas boom, and the fading of commerican nuclear power's 'renaissance', this ninth edition offers needed currency and relevancy for any environmental politics course." -- Back cover.
1. After earth day -- 2. Making policy : the process -- 3. Making policy : institutions and politics -- 4. Common policy challenges : risk assessment and environmental justice -- 5. More choice : the battle over regulatory economics -- 6. Command and control in action : air and water pollution regulation -- 7. A regulatory thicket : toxic and hazardous substances -- 8. Energy : America's energy politics in transformation -- 9. 635 million acres of politics : the battle for public lands -- 10. Climate change, domestic politics and the challenge of global policy making
Includes bibliographical references and index
Keywords: Environmental policy -- United States